2007
DOI: 10.1063/1.2430768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of single-crystalline PbTiO3 nanowire growth via surfactant-free hydrothermal method

Abstract: In this work, we present the results obtained in fabrication and characterization of single-crystalline lead titanate nanowires synthesized by surfactant-free hydrothermal method at 200°C. The as-prepared samples were characterized by means of x-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy (TEM), high-resolution TEM, selected-area electron diffraction, x-ray photoelectron spectroscopy (XPS), thermogravimetry and differential thermal analysis, Fourier transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
0
42
1
1
Order By: Relevance
“…The remarkable cell shrinking and tetragonality decreasing induced by size effect have also been observed in the BaTiO 3 and SrTiO 3 nanostructures prepared through surfactant system [2,7]. In contrast, the PT nanorod by surfactant-free method shows less change in lattice than crystal, though the size effect was observed as well [6]. Therefore, we suggest that the both the point-initiated growth kinetics of nanorods and the surfactants used in synthesis process contribute to the enhancing of the size effect.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The remarkable cell shrinking and tetragonality decreasing induced by size effect have also been observed in the BaTiO 3 and SrTiO 3 nanostructures prepared through surfactant system [2,7]. In contrast, the PT nanorod by surfactant-free method shows less change in lattice than crystal, though the size effect was observed as well [6]. Therefore, we suggest that the both the point-initiated growth kinetics of nanorods and the surfactants used in synthesis process contribute to the enhancing of the size effect.…”
Section: Resultsmentioning
confidence: 82%
“…Variety of techniques, such as solution-phase decomposition [1,3], hydrothermal [5,6], flux [2], template [4,7], microemulsion [8] and electro-spinning [9] methods, have been developed to synthesize them. And many further researches are directed towards the detailed experimental investigations on their size-dependent properties [3,4,6,10]. As an important perovskite oxide of excellent ferroelectric and optoelectronic characters, PT has been studied theoretically and experimentally in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Pure PbTiO 3 is known to have a sharp ferroelectric to paraelectric transition around 763 K (Curie temperature) accompanied by a structural transition from polar tetragonal to non-polar cubic phase [28]. This structural phase transition manifests as a sharp and frequency independent peak in dielectric permittivity versus temperature plot.…”
Section: Resultsmentioning
confidence: 99%
“…Gu, et al reported characterization of single-crystalline lead titanate nanowires using photoluminescence spectroscopy, and ultraviolet-visible spectroscopy [26,27]. The nanowires were synthesized by surfactant-free hydrothermal method at 200 o C. The nanowires with uniform diameters of about 12 nm and lengths up to 5 um, exhibit a tetragonal perovskite structure without impurity phases.…”
Section: Photoluminescence In Ferroelectric Nanowires Nanotubes Andmentioning
confidence: 99%